Dual‐band asymmetric circular polariser based on fission transmission of linearly polarised wave. Issue 8 (16th May 2018) - Mangi, Farman Ali; Xiao, Shaoqiu; Yao, Zhixin; Memon, Imran; Kakepoto, Ghulam Fatima
Abstract : A dual‐band asymmetric circular polariser based on fission transmission of linearly polarised (FTLP) wave is presented. First, the novel approach of FTLP wave is introduced to transform linearly polarised wave into the circularly polarised wave with strong circular dichroism effect. It means that the x ‐linearly polarised incident wave converts into two orthogonal components E x t and E y t through the bottom layer of the structure along the + z direction. The two decomposed components are used as excitation source for the upper layer and converted into four linear transmission components at the end of the structure. The phenomena of incidence and transmission sequence of the orthogonal components constitute the chain transmission of the linearly polarised wave. The designed structure achieves dual‐band circular polarisation with asymmetric transmission wave emission by the principle of FTLP wave. The transformation behaviour for circular polarisation is illustrated by the surface currents distribution. The proposed structure achieves a right‐handed circularly polarised wave and left‐handed circularly polarised wave with high transmission at 14.40–15.70 GHz and at 16.0–17.0 GHz, respectively. The axial ratio bandwidth of 11.76 and 6.86% is obtained at dual band. The simulated and measured results exhibit good correspondence.